2020
DOI: 10.1037/str0000145
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of posttraumatic stress disorder’s E2 criterion: Development, pilot testing, and validation of the Posttrauma Risky Behaviors Questionnaire.

Abstract: To capture the functional role of reckless and self-destructive behaviors (RSDBs) in posttraumatic stress disorder’s (PTSD) symptomatology, the E2 symptom was added in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. However, the lack of a validated, comprehensive, and clinically useful measure is a significant barrier to the assessment/treatment of PTSD’s E2 criterion. We developed and validated a measure assessing PTSD’s E2 criterion (Posttrauma Risky Behaviors Questionnaire [PRBQ]).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…However, these differences should be taken into consideration when interpreting results as they may contribute to conflicting findings. Additionally, this review defined risky behaviors according to categories of behavior identified by empirically validated measures (Contractor et al, in press; Sadeh & Baskin-Sommers, 2017; Weiss et al, 2018). Thus, our list of risky behaviors may not have been exhaustive.…”
Section: Discussionmentioning
confidence: 99%
“…However, these differences should be taken into consideration when interpreting results as they may contribute to conflicting findings. Additionally, this review defined risky behaviors according to categories of behavior identified by empirically validated measures (Contractor et al, in press; Sadeh & Baskin-Sommers, 2017; Weiss et al, 2018). Thus, our list of risky behaviors may not have been exhaustive.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we excluded 97 participants who were missing data on all measures and 11 participants who did not endorse a traumatic event on the Life Event Checklist for DSM‐5 (LEC‐5; Weathers, Blake, et al., 2013). Finally, we excluded 47 participants who were missing more than 30% of item‐level data on the PTSD Checklist for DSM‐5 ([PCL‐5] i.e., six items or more; Weathers, Litz, et al., 2013) or the Posttrauma Risky Behaviors Questionnaire ([PRBQ] i.e., five items or more; Contractor, Weiss, Kearns, Caldas, & Dixon‐Gordon, 2019). The final effective sample size was 417 participants.…”
Section: Methodsmentioning
confidence: 99%
“…The last two items assess functional impairment due to RSDBs and the relation of the RSDB frequency to the onset of the worst trauma. The PRBQ demonstrates good psychometrics (Contractor et al, 2019(Contractor et al, , 2020(Contractor et al, , 2021); Cronbach's alpha in the current study = .92.…”
Section: Methodsmentioning
confidence: 50%
“…This study presents both theoretical and clinical implications. Previous literature has noted that various posttrauma health outcomes may be driven by common risk factors (Contractor et al, 2019;Shaw et al, 1992); we advance this literature by suggesting that emotion dysregulation may be one such common mechanism underlying both PTSD and posttrauma RSDBs. Relatedly, this research supports the importance of targeting emotion dysregulation in trauma treatments given its central role in enhancing/maintaining posttrauma RSDBs among individuals with varied PTSD symptoms (Ehring & Quack, 2010).…”
Section: Limitations Future Directions and Implicationsmentioning
confidence: 55%